PERAN MAJELIS TAKLIM WAL MAULID AR RIDWAN BATU DALAM MEMBINA AKHLAK REMAJA DI KELURAHAN NGAGLIK KOTA BATU - Vendi Hardianto (VICRATINA, 2019)
Majelis Taklim is a non-formal institution to seek religious knowledge. The existence of majelis taklim gives influence in the surrounding environment. In addition to the assembly of religious assemblies it also means the community, orientation and life insights into religion and society, forming solidarity, filling in leisure time. The  position as a non-formal Islamic education institution that allows a varied role. By embracing teenagers, Majelis Taklim Arridwan Batu conduct activities to fortify adolescent morality.  Kata Kunci : majelis, akhlak, remaja